2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649456
|View full text |Cite
|
Sign up to set email alerts
|

Networking and plug-and-play of bedside medical instruments

Abstract: Medical device manufacturers continuously improve instruments with more capabilities at the point of care such as the bedside, operating room, intensive care unit, or emergency room. The instruments are in turn becoming more sophisticated; however, the operation of an instrument is still expected to be locally done by authorized medical personnel. The measurements from these instruments are stored using archaic methods such as a patient history record on a paper. The access to these records is cumbersome and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Pre-and post-tests demonstrated that this checklist alone resulted in nearly one-third fewer complications and deaths post-surgery in major hospitals and hospital systems throughout the country (Haynes et al, 2009). Many research teams are also developing secure, Web-based platforms that connect multiple interoperable devices (e.g., in the operating or recovery room) to facilitate enhanced data liquidity that can dramatically improve real-time decision making, all the while ensuring security and privacy safeguards for the individuals whose data are being transferred (Goldman et al, 2005;Thongpithoonrat et al, 2008).…”
Section: Transformations In Care Deliverymentioning
confidence: 99%
“…Pre-and post-tests demonstrated that this checklist alone resulted in nearly one-third fewer complications and deaths post-surgery in major hospitals and hospital systems throughout the country (Haynes et al, 2009). Many research teams are also developing secure, Web-based platforms that connect multiple interoperable devices (e.g., in the operating or recovery room) to facilitate enhanced data liquidity that can dramatically improve real-time decision making, all the while ensuring security and privacy safeguards for the individuals whose data are being transferred (Goldman et al, 2005;Thongpithoonrat et al, 2008).…”
Section: Transformations In Care Deliverymentioning
confidence: 99%
“…The key feature for reducing time seems to be the direct transmission of the obtained vital signs, realized by the sensor network. Although most of the sensor networking research is dedicated to remote sensing and ubiquitous health support in the home environment as summarized in [17], some [18 -20] have attempted at introducing such wireless-ready devices into hospitals and some [21][22][23][24] have tried connecting them to EPR. Once sensor networks are connected to EPR, the obtained vital signs are directly transmitted to patient records.…”
Section: Figure 12mentioning
confidence: 99%
“…Sensor networks [17][18][19][20][21][22][23][24] where sensors provide obtained data for certain information system over mainly wireless communication channels may be the solution to make whole vital signs input task quicker and more efficient. However, a simple introduction of sensor networks will not reduce the input tasks, because the sensors themselves cannot provide any information about the data source, that is, a patient from whom the vital sign is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them just concentrate on the advancement of the sensor network infrastructure to connect various devices to conventional monitoring system available in an intensive care unit. Few [22]- [24] care about communication with an electric patient record. However, a simple conventional monitoring system is not sufficient to smoothen the clinical process; we need to consider how the wireless-ready sensor is used.…”
Section: Networked Digital Cameramentioning
confidence: 99%